Comparison between upfront surgery vs salvage surgery following definitive chemoradiation in the treatment of potentially curable locally advanced oral cavity cancer: a retrospective study - Shanmugam, Subbiah; Shivakumar, Aravind (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: We conducted a study to compare the outcomes of upfront surgery and salvage surgery following definitive chemoradiation in locally advanced oral cavity squamous cell carcinoma. This study aims to compare the short-term outcomes (postoperative morbidity, recurrence) & long-term outcomes (overall survival, disease-free survival) between upfront surgery and salvage surgery following definitive chemoradiation in locally advanced oral cavity squamous cell carcinoma. Methods: A total of sixty patients with locally advanced oral cavity squamous cell carcinoma (T4a, N1-N2b) were retrospectively analyzed between January 2021 and August 2023. Thirty patients underwent upfront surgery followed by adjuvant radiation (group 1) while another thirty patients underwent salvage surgery following definitive chemoradiation (group 2) (radiation dose- 66-70 Gy) Results: Morbidity was found to be significantly higher in the salvage surgery group (group 2) when compared to the upfront surgery group (group 1) with a p value of 0.003. There was no statistical significance between the two groups in terms of disease-free survival and overall survival. Conclusions: This retrospective study shows that there are no significant differences in overall survival and disease-free survival amongst patients of locally advanced oral cavity squamous cell carcinoma treated with upfront surgery and salvage surgery following definitive chemoradiation. Morbidity is significantly higher in the salvage surgery group.